2020
DOI: 10.52321/geolbalc.49.2.39
|View full text |Cite
|
Sign up to set email alerts
|

The problems of the post-Cenomanian tectonic evolution of the central parts of the Sredna Gora Zone. The wrench tectonics – how real is real?

Abstract: The Sredna Gora Zone holds a unique place in the tectonic subdivisions of the Balkanide orogen and its evolution is still a subject of debate. In the last twenty years, the idea of strike-slip-related evolution of the zone has been invoked. However, for the moment, the number of thorough studies where such a scenario is envisaged is limited, and substantial evidence based on detailed fieldwork is still missing. In this article, we discuss some of the major problems of the suggested wrench tectonic concept in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…The Late Jurassic-Early Cretaceous ductile right-lateral shearing observed in the southern part of the Sakar Unit (Gerdjikov, 2005), as well as in the North Rhodope Unit (Naydenov et al, 2013), could be related to the formation of a major wrench zone separating the opposite-vergent thrust belts of the Rhodope to the south and the Strandzha, Sredna Gora and Balkan zones to the north (Fig. 6b, c; Naydenov et al, 2013) as it was suggested also for the Late Cretaceous-Paleogene evolution of the Maritsa fault zone (Kounov and Gerdjikov, 2020).…”
Section: Wrench and Retro-wedge Lower Unitsmentioning
confidence: 67%
“…The Late Jurassic-Early Cretaceous ductile right-lateral shearing observed in the southern part of the Sakar Unit (Gerdjikov, 2005), as well as in the North Rhodope Unit (Naydenov et al, 2013), could be related to the formation of a major wrench zone separating the opposite-vergent thrust belts of the Rhodope to the south and the Strandzha, Sredna Gora and Balkan zones to the north (Fig. 6b, c; Naydenov et al, 2013) as it was suggested also for the Late Cretaceous-Paleogene evolution of the Maritsa fault zone (Kounov and Gerdjikov, 2020).…”
Section: Wrench and Retro-wedge Lower Unitsmentioning
confidence: 67%
“…The north-vergent translations along the zone led to the deformation of the Upper Cretaceous sequences of the Chelopech Basin (Fig. 2; e.g., Kounov and Gerdjikov, 2020).…”
Section: Alpine Tectonic Zonesmentioning
confidence: 99%
“…Any original volcanic equivalents have been removed by erosion. A second Alpine compressional event affected the area after the Maastrichtian and caused substantial thrust faulting and folding of the Upper Cretaceous sequences [30,[42][43][44].…”
Section: Geological Settingmentioning
confidence: 99%